Celebrity Endorsement Attributes and Consumer Purchase Decisions in Indonesia’s Electric Vehicle Market - Rafi Amani Muflih Rahardi; Wika Novita Sari; Aisyah Bella Ayuningtyas (Penerbit Goodwood, 2026)
Purpose: This study investigates the influence of celebrity endorsement attributes visibility, credibility, attractiveness, and power on consumer purchase decisions for Electric Vehicles (EVs) in Indonesia, where adoption remains relatively low despite incentives and growing environmental awareness. Methodology/approach: A quantitative survey was conducted with 385 Indonesian social media users. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationships between endorsement attributes and purchase behavior. Results: The model explains 70.3% of the variance in purchase decisions. Power and visibility exerted the strongest influence, followed by credibility and attractiveness. These results indicate that consumers are more persuaded by endorsers who demonstrate authority, have a broad media presence, and possess authentic reputations, while attractiveness provides supplementary appeal. Conclusions: The findings highlight the central role of celebrity endorsements in bridging the gap between consumer awareness and actual EV adoption. Collaboration with credible and visible public figures can accelerate sustainable consumption and position EVs as aspirational products in Indonesia. Limitations: This study focused only on Indonesian social media users and excluded other potential determinants of EV adoption, limiting generalizability. Contributions: This research extends endorsement theory into sustainable marketing and provides practical guidance for firms and policymakers to design effective communication strategies that leverage celebrity endorsements to promote eco-friendly innovations, especially electric vehicles.